CONSUMER DECISIONS IN CHOOSING BIORE PRODUCTS (CASE STUDY OF BIORE BODY FOAM PRODUCT SALES IN YOGYA CIWALK BANDUNG) - Hapsari, Ayuningtyas Y.; Aji, Yoga Prasetya; Hadian, Dodi Rizqi; Guspita, Meylin Mega; Maulana, Fikri Nur; Saputro, Tanto Duwi; Roespinoedji, Djoko (CENTRAL ASIA AND THE CAUCASUS, 2022)
Personal care products are consumer goods products, consumables that are used daily. PT. Kao Indonesia is one of the companies that makes this consumable product, by issuing the Biore Body Foam brand, this product is sold in the market with approximately 15 different fragrance variants according to consumer needs. However, based on sales data in the field, Biore's bath soap products have actually decreased over the last two years, even though there is always a demand to add more places to display their product variants. This research is aimed at prospective consumers at the Yogya Ciwalk supermarket, Bandung, as many as 110 respondents, they will be asked to fill out an online form which will be automatically recorded, respondents will be asked to answer several questions about product variants of Biore bath soap and how the layout is made. is in the supermarket, so it will be seen how much influence each of these variables has on consumer decisions to buy Biore bath soap products. The method used in this research is descriptive verification method and uses multiple regression analysis tools. And finally, partial and simultaneous testing will also be carried out so that research conclusions can be drawn based on the data obtained from the population.